Rekombinan Vascular Endothelial Growth Factor-121 Menekan Ekspresi Heat Shock Protein-70 pada Plasenta Mencit Model Preeklampsia (VASCULAR ENDOTHELIAL GROWTH FACTOR-121 RECOMBINANT DEPRESSIS HEAT SHOCK PROTEIN-70 EXPRESSION IN PREECLAMPSIA MICE PLACENTA - Sulistyowati, Sri; Tanjung, Lungguk Helen Alfian; Respati, Supriyadi Hari; Soetrisno, Soetrisno (Jurnal Veteriner, 2018)
Preeclampsia has remained a major cause of morbidity and maternal-perinatal mortality. Oxidative stress that occurs in preeclampsia increases HSP-70 expression. Therefore, VEGF therapy is expected to recover this oxidative stress. This research aimed to determine the role of VEGF-121 recombinant on HSP-70 expression in mice model of preeclampsia. This research was an explanatory study conducted at Animal Cage Experiment, Faculty of Veterinary Medicine, Airlangga University. The samples were 30 mice that were divided into 3 groups, namely a group of 10 normal pregnant mice, a group of 10 mice model of preeclampsia, and a group of 10 mice model of preeclampsia with VEGF-121 recombinant therapy. On the 16th day of gestation, HSP-70 expressions in the placenta of all mice were examined using immunohistochemical methods. The data were analyzed using Kruskall-Wallis test of SPSS program. The mean of HSP-70 expression in normal pregnancy group was 1.69 ± 0.68, in preeclampsia model group was 3.50 ± 0.95 with p = 0.00, and in preeclampsia model group with VEGF-121 recombinant therapy was 2.24 ± 0.84 with p = 0.00. In short, VEGF-121 recombinant has a role in lowering HSP-70 expression in mice placenta model of preeclampsia